2013
DOI: 10.1055/s-0039-3401717
|View full text |Cite
|
Sign up to set email alerts
|

Third head of gastrocnemius - a case report

Abstract: Gastrocnemius is a superficial muscle of the posterior compartment of leg. It usually arises by two heads- a medial and a lateral head. A third head of Gastrocnemius has been reported to occur in 2.9 - 5.5% of subjects. This anomaly has been implicated as a cause for popliteal vessel entrapment syndrome.Variations of the heads of origin of Gastrocnemius muscle were studied in 20 lower extremities of ten adult cadavers during routine Popliteal Fossa dissection at Sri Manakula Vinayagar Medical College and Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a similar study conducted on Indian population, the prevalence rate was found to be 80%. 10 According to literature, the three-headed gastrocnemius is the most common variation of gastrocnemius muscle. Various authors have described its prevalence rate to be as 2.9%-5.5% (Bergman 1995), 7.5% (Arce 2008), 1.9% (Koplas et al, 2009), 20% (Shalini et al, 2013) and 13.3% (Ashaolu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted on Indian population, the prevalence rate was found to be 80%. 10 According to literature, the three-headed gastrocnemius is the most common variation of gastrocnemius muscle. Various authors have described its prevalence rate to be as 2.9%-5.5% (Bergman 1995), 7.5% (Arce 2008), 1.9% (Koplas et al, 2009), 20% (Shalini et al, 2013) and 13.3% (Ashaolu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%